Effect of spoiler columns on heat transfer performance of aluminum nitride-based microchannel heat sink. Issue 24 (15th December 2022) - Wei, Jiawei; Chen, Ni; Li, Liang; Liu, Jiawei; Zhao, Junyi; Wang, Chaoran; He, Ning
Abstract: Microchannel heat sinks (MCHSs) are among the most effective solutions for high-power heating elements; aluminium nitride (AlN) is widely used in various heat sinks owing to its high thermal conductivity. The study aims to investigate the effect of the spoiler column shape, number of rows, and position of the inlet/outlet on the temperature and pressure drop of AlN-based microchannel heat sink using a thermal fluid structure coupling simulation. The results showed that the circular spoiler column had the best dredging effect on the eddy current, which greatly improved the local Nusselt number and heat transfer efficiency. The maximum temperature of the heat sink with circular spoiler columns was 6.53 K lower than that without the spoiler column. The average flow velocity and heat transfer efficiency increased with an increase in the number of spoiler columns and the convective heat transfer area. However, the flow resistance and pressure drop between the inlet and outlet raised. When the inlet and outlet were arranged at the centreline, the flow velocity distribution in the heat sink is more uniform, and the maximum temperature was 160.78 K lower than that on the upper side. Heat transfer experiments were carried out by using three kinds of AlN-based microchannel heat sinks, which was machined by the pickling-assisted laser method. The heat transfer experiments showed that the error between simulation results and test data was less than 0.1%.